Fairness, technology and the ethics of Paralympic sport classification - McNamee, M.; Parnell, R.; Vanlandewijck, Y. (European Journal of Sport Science, 2021)
Fairness in sport is a widely shared meritocratic norm. Its application is usually restricted to equality of opportunity to compete for victory. Paralympic sports lay down a further challenge in that equality of opportunity must be shaped by considerations of fairness, evidenced by the development of discrete competition categories to construct fair and meaningful contests. In this article, we extend these philosophical ideas to consider how Fair Equality of Opportunity might operate in the context of Paralympic sports classification. We articulate three conceptions of fairness relevant to these sports: (i) background fairness; (ii) procedural fairness; and (iii) stakes fairness. We critically review the International Paralympic Committee`s Policy on Sport Equipment in relation to the first two conceptions and argue that greater clarification, theorization and rule modification is required if physical prowess, as opposed to equipment technology, is to be assured as the dominant determinant of Paralympic athletic success.